Respostas

2014-02-01T16:14:26-02:00
Vou fazer por Bhaskara mas também pode ser feito por soma e produto.

x² - 5x + 6 = 0
a= 1  b= -5    c= 6

Δ= b² -4ac
Δ = (-5)² - 4 . 1 . 6
Δ = 25 - 24
Δ = 1

x = -b ±√Δ        
        2a

x = -(-5) ± √1
         2

x '= -(-5) + √1
           2
x' = 5 + 1/ 2
x' = 3

x "= -(-5) - √1
           2
x" = 5 - 1/2
x" = 2



4x² - 29x + 25 = 0
a= 4 b= -29 c= 25

Δ= b² -4ac
Δ= (-29)² - 4.4.25
Δ = 841 - 400
Δ = 441

x = -b ±√Δ         
        2a

x = -(-29) ±√441         
          8

x' = 29 + 21/8
x' = 50/8
x' = 25/4

x" = 29 - 21/8
x" = 8/8 
x" = 1



x (x - 1) = 156
x² - x - 156= 0
a= 1 b= -1 c= -156

Δ= b² -4ac
Δ = 1 - 4 . 1 . (-156)
Δ = 1 + 624
Δ = 625

x = -b ±√Δ         
        2a

x = -(-1) ± √625         
            2

x' = 1 + 25/2
x' = 26/2
x' = 13

x" = 1 - 25 /2
x" = -24/2
x" -12

Espero ter ajudado (:
1 5 1
2014-02-01T16:38:20-02:00
x²-5x+6=0
Δ = b² -4ac
Δ = (-5)² -4 *1 * 6
Δ = 25 -24
Δ = 1
x' = (-b + √∆)/ 2a
(-(-5) + 1)/2 * 1
(5 + 1)/2
6/2
3
x'' = (-b - √∆)/ 2a
(-(-5) - 1)/2 * 1
(5 - 1)/2
4/2
2

S={3,2}.

4x
²-29x+25=0
Δ = b² -4ac
Δ = (-29)² -4 *4 * 25
Δ= 841 -400
Δ = 441
x' = (-b + √∆)/ 2a
(-(-29) + 21)/2 * 4
(29 + 21)/8
50/8
6,25
x'' = (-b - √∆)/ 2a
(-(-29) - 21)/2 * 4
(29 - 21)/8
8/8
1

S={50/8,1}


x(x-1)=156
x
²-x=156
x²-x-156=0
Δ = b² -4ac
Δ = (-1)² -4 *1 * (-156)
Δ = 1 + 624
Δ = 625
x' = (-b + √∆)/ 2a
(-(-1) + 25)/2 * 1
(1 + 25)/2
26/2
13
x'' = (-b - √∆)/ 2a
(-(-1) - 25)/2 * 1
(1 - 25)/2
-24/2
-12

S={-12,13}
1 1 1